Path Integral Solutions of the PT-Symmetric and Non-Hermitian q-deformed Eckart Plus Modified Hylleraas Potential (Global Journal of Science Frontier Research, 2018)
In this study, the wave functions and the energy spectrum of the PT-Symmetric and non-Hermitian q-deformed Eckart plus modified Hylleraas potential are studied using Feyman's Path In-tegral method. The kernel and Green.s Function for PT-Symmetric and non-Hermitian qdeformed Eckart plus modified Hylleraas potential is analytically derived by transforming spacetime. The results are discussed for the different parameters of the potential.
Keywords: PT -symmetry; non-hermitian; path integral; exponential potentials; pt-symmetric and non hermitian potentials; pt-symmetric and non-hermitian q-deform